Early increased cell proliferation compensates subsequent hypoplasia of the ossicle - Kawasaki, Katsushige; Kawasaki, Maiko; Sari, Finsa Tisna; Utama, Vanessa; Kesuma, Alex; Fukushima, Makoto; Saito, Naoaki; Suda, Daisuke; Kudo, Takehisa; Fujita, Akira; Nihara, Jun; Franco, Brunella; et al. (Frontiers in Cell and Developmental Biology, 2025)
Ossicles are essential structures for normal sound conduction from the external environment to the inner ear. Proper formation of the ossicles is required for normal hearing, and ossicular deformities lead to hearing loss. We identified ossicular hypoplasia in mice with mesenchymal conditional deletion of the primary cilia molecule (Ofd1fl;Wnt1Cre and Ift88 fl/fl;Wnt1Cre). Hh signaling activity and cell proliferation were significantly downregulated in ossicle primordia of Ofd1fl;Wnt1Cre mice from E11.5. To restore Hh signaling in Ofd1fl;Wnt1Cre mice, we crossed R26SmoM2fl mice (a constitutively active form of Smo) with Ofd1fl;Wnt1Cre mice. Ossicular hypoplasia was partially rescued in Ofd1fl;Wnt1Cre;R26SmoM2fl mice. However, Hh signaling activity was not restored after E11.5. Instead, Hh signaling activity and cell proliferation were significantly increased in Ofd1fl;Wnt1Cre;R26SmoM2fl mice at E10.5, when these were not altered in Ofd1fl;Wnt1Cre mice. To confirm whether molecular changes at E10.5 rescue subsequent hypoplasia, SAG (agonist of Hh signaling) was applied to Ofd1fl;Wnt1Cre mice at E9.5. A similar rescue could be observed in Ofd1fl;Wnt1Cre mice with SAG application. Thus, early increased cell proliferation could compensate subsequent hypoplasia of ossicle formation. Our results may provide clues for possible future treatment in familial hearing loss due to hypoplasia of the ossicles.